Hymen injuries in medico-legal evaluation of sexual integrity - Pacheco D, José (2005)
Objective: To determine hymenal injuries and morphologic variants. Materials and Methods: Prospective and descriptive study done during July and August 2005. Results: There were 284 examinations for sexual violation denunciations; 80,3% corresponded to children and adolescents. The main findings were: dilatable hymen (36,9%), integral hymen (34,8%), old ruptures (13.6%), dilatable hymen with recent injuries (4,5%), recent ruptures (1,5%), among others. Conclusions: The elastic hymen with ample orifice originates difficulty in the recognition of recent injuries. An ‘accommodating’ or ‘dilatable’ hymen does not categorically determine the introduction of the penis or other member of the body or object. Legal Medicine teaches on hymenal variants and main injuries so that any examiner has enough technical and scientific knowledge at the time of crediting his findings to judicial or fiscal authorities.